Port cybersecurity and threat: A structural model for prevention and policy development - Chalermpong Senarak (Asian Journal of Shipping and Logistics (AJSL), 2021)
Most port operators have increasingly integrated cybertechnology into port activities to increase their competitiveness; unfortunately, this digitalization becomes the major vulnerability for the emerging cyberthreat. To help port policymakers develop cybersecurity measures, this study conceptualized and developed three dimensions of port cybersecurity hygiene (i.e. human, infrastructure, and procedure factors) and investigated the relationships between port cybersecurity hygiene and cyberthreats (i.e. hacktivism, cyber criminality, cyber espionage, cyber terrorism, and cyber war). A questionnaire survey was used to collect data from all international container port operators and shipping lines with branches in Thailand, and the proposed relationships were tested by structural equation modeling. The results indicated that container ports tended to encounter hacktivism when their human, infrastructure, and procedure factors were vulnerable. The weakness of the human factor could also lead to cyber terrorism, while the deficiency of the infrastructure factor could lead to cyber criminality. Moreover, container ports were likely to be harmed by cyber espionage if their procedure factor was poorly implemented. Hence, the provision of training and education to all port workers, including top executives, managers, and supervisors, are necessary to ensure a cyberthreat-awareness culture at all organizational levels. Improving cybersecurity equipment could prevent unauthorized access to port business data and keep important information secure, while the ISPS Code-based procedures and other preventive measures should be strictly implemented by container ports to reduce the risk of cyberthreats.
Keywords: 650; Cyberthreat; Port cybersecurity hygiene; Cybertechnology; Prevention and policy development; Port digitalization; Structural equation modeling